"Effect of local application of simvastatin in bone regeneration of peri-apical defects-a clinico-radiographic study - Sweety Gupta; Promila Verma; Aseem Prakash Tikku; Anil Chandra; Rakesh Kumar Yadav; Ramesh Bharti; Rhythm Bains (Elsevier, 2020)
Objective: The present study evaluates and compares the effectiveness of Simvastatin (SIM), Hydroxyapatite (HA), and platelet-rich fibrin (PRF) in bone regeneration of periapical defects. Material& method: Thirty-nine patients were selected and randomized into three groups, Group 1: HA (n = 13), Group 2: PRF (n = 13), Group 3: SIM (n = 13). After completion of RCT and apicoectomy, the grafts were placed locally in the defect and sutured. Results: At the end of twelve months, postoperative symptoms and radiographic analysis assessed the outcome of the treatment Conclusion: Intragroup analysis of CBCT- Periapical Index (PAI) scores at 6th and 12th month revealed a significant change in the SIM group (p = 0.018 and 0.001 respectively), compared to PRF (p = 0.026 and 0.001 respectively) and HA (p = 0.053 and 0.039 respectively). Intergroup analysis of change in the level of CBCT-PAI score was highly significant (p = 0.003).SIM caused a more considerable change in the level of CBCT-PAI score compared to other groups, thereby indicating a faster rate of bone regeneration.